Caterflies and ice - Citro, Asia (Citro, Asia. Zoey and Sassafras., 2017)
"When an unexpected snowstorm causes trouble for the magical creatures of the forest, Zoey and Sassafras come to the rescue. But their first attempt to save trapped caterfly eggs results in a big mistake. Can they figure out a way to fix things before the baby caterflies hatch?"--Jacket.